Exploring Two Years of Stunting Trends: Insights from Tidore Kepulauan - Sukmawati Hasan, Diana; Muhammad, Sinta (PT. Sangadji Media Publishing, 2024)
Stunting, as a complex issue, demands a serious and comprehensive approach. Accelerating efforts to reduce stunting is imperative and requires collaboration from all stakeholders, including the Tidore government, private sector, community, and families. Furthermore, addressing this issue necessitates extensive longitudinal research to investigate its prevalence and influencing factors. To tackle this, a crucial study is essential to unveil the prevalence trends of stunting from 2022 to 2023, covering the last two years in the Tidore Kepulauan. The primary goal of this research is to provide a comprehensive overview of stunting trends in Tidore through long-term analysis, exploring prevalence fluctuations. Employing a descriptive statistical approach, this study relies on numerical data as its primary foundation, focusing on in-depth descriptive analysis of stunting prevalence trends in the Tidore Kepulauan over the last two years. Data from the Directorate General of Regional Development's website reveals significant variations among villages in 2022. Villages like Gurabati (1.2%), Toloa (2.1%), and Maregam (3.8%) exhibit low rates, whereas Topo (45.5%), Topo Tiga (23.1%), and Maitara Tengah (20.6%) have high rates. Specific efforts are needed in high-prevalence villages to improve child nutrition and overall community well-being. The 2023 prevalence data shows significant variations among villages, with some areas displaying alarmingly high rates. Descriptive statistical analysis links stunting in the Tidore Kepulauan to several key factors. Malnutrition (32.4%), inadequate nutritional intake, and prenatal malnutrition (28.2%) are major contributors. Genetic factors (16.2%), poor hygiene (4.8%), and viral/bacterial infections (4.1%) also play roles. Lower economic levels and other factors contribute in smaller proportions (2.8% and 3.0% respectively). Although 8.5% of respondents are unaware of the causes, this analysis provides a comprehensive overview of factors that need attention to combat stunting in the Tidore Kepulauan.